Global status of lentil production with special reference to India - REDDY, A AMARENDER; MALIK, D P; DEVI, MONIKA (The Indian Journal of Agricultural Sciences, 2022)
India needs to increase it pulse production to meet the growing demand. Lentil is one of the important pulse crop grown in winter season in tropical and subtropical regions of world. The study analysed the trends in production and trade scenario in India and globally from 2000–2018 and came out with strategies for increasing production. The state-wise analysis was carried out for major producing states like Madhya Pradesh, Uttar Pradesh, Bihar, West Bengal and Rajasthan from 2000–2019. The lentil production in the world reached around 6.33 million tonnes in 2018 with an annual growth rate of 4.4% since last 20 years. Asia alone contributed more than half of total global lentil production. The share of American and Oceania regions in global lentil production increased in recent years. There was increase in lentil yield in recent years in Africa, Asia and American regions due to adoption of improvedproduction technologies. India and Canada together contributed more than 50% of total world lentil production. Lentil yield was highest in Canada (1425 kg/ha), lowest in India (744 kg/ha) in 2018. The lentil production in India touched 1.47 million tonnes with larger share contributed by Bihar, Madhya Pradesh, Rajasthan, Uttar Pradesh and West Bengal in 2018. India is the leading importing nation sharing more than one-fourth of total world import during last five years. Adoption of drought, heat, biotic stresses tolerant high yielding cultivars are required to meet estimated demand of 2.00 million tonnes by 2030.Keywords: Agricultural production, Economics, Legumes, Lentil, Policy Interventions, Trade